Nutlin-3, A p53-Mdm2 Antagonist for Nasopharyngeal Carcinoma Treatment - Yee-Lin, Voon; Pooi-Fong, Wong; Soo-Beng, Alan K. (Mini Reviews in Medicinal Chemistry, 2018)
Nasopharyngeal carcinoma (NPC) is a form of head and neck cancer of multifactorial etiologies that is highly prevalent among men in the population of Southern China and Southeast Asia. NPC has claimed many thousands of lives worldwide; but the low awareness of NPC remains a hindrance in early diagnosis and prevention of the disease. NPC is highly responsive to radiotherapy and chemotherapy, but radiocurable NPC is still dependent on concurrent treatment of megavoltage radiotherapy with chemotherapy. Despite a significant reduction in loco-regional and distant metastases, radiotherapy alone has failed to provide a significant improvement in the overall survival rate of NPC, compared to chemotherapy. In addition, chemo-resistance persists as the major challenge in the management of metastatic NPC although the survival rate of advanced metastatic NPC has significantly improved with the administration of chemotherapy adjunctive to radiotherapy. In this regard, targeted molecular therapy could be explored for the discovery of alternative NPC therapies. Nutlin-3, a small molecule inhibitor that specifically targets p53-Mdm2 interaction offers new therapeutic opportunities by enhancing cancer cell growth arrest and apoptosis through the restoration of the p53-mediated tumor suppression pathway while producing minimal cytotoxicity and side effects. This review discusses the potential use of Nutlin-3 as a p53-activating drug and the future directions of its clinical research for NPC treatment.
Keywords: Apoptosis